Variation Orders and It’s Procedure for Hydropower Construction - Neupane, Abhushan (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
There is lots of construction going in Nepal, of which hydropower construction is also moving in significant pace. As the design and drawings prepared during development of the hydropower project may not fully reflect the construction situation, due to the different circumstances led by the Employer, Engineer or Contractor working for the Project. It has been observed globally that the design during project preparation in hydropower projects needs revision during implementation; hence the basic understanding of Variation Orders is very important to the hydropower professionals. HYDRO Nepal Journal Journal of Water Energy and Environment Issue: 21, July, 2017 Page: 15-16 Upload Date: July 18, 2017